Program Makan Gratis di Masjid Pemuda Indonesia sebagai Strategi Inovasi untuk Meningkatkan Kecintaan Generasi Muda kepada Masjid - Mirza, Ghaitsa Shazia; Bramayudha, Airlangga (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2024)
This study aims to explore and analyze the innovation strategies implemented by the Masjid Pemuda Indonesia in Surabaya in increasing the love of the younger generation for the mosque. The participation and love of the younger generation of Muslims in religious activities in the mosque often decreases along with the development of the times and changes in lifestyle. Therefore, an innovative approach is needed to attract their interest and involvement. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with mosque administrators, direct observation, and documentation analysis. The results of the study indicate that effective innovation strategies include organizing programs that are in accordance with the interests of the younger generation, utilizing social media as a means of communication and promotion, and collaborating with local communities. The implementation of this strategy has been proven to increase the presence and active participation of the younger generation in mosque activities. These findings are expected to be a reference for other mosques in developing relevant strategies to enggage the young generation in religious environments.Key Words: free meal, young generation, love the mosqueABSTRAKPenelitian ini bertujuan untuk mengeksplorasi dan menganalisis strategi inovasi yang diterapkan oleh Masjid Pemuda Indonesia di Surabaya dalam meningkatkan kecintaan generasi muda kepada masjid. Partisipasi dan kecintaan generasi muda Muslim dalam kegiatan keagamaan di masjid seringkali mengalami penurunan seiring dengan perkembangan zaman dan perubahan gaya hidup. Oleh karena itu, diperlukan pendekatan inovatif untuk menarik minat dan keterlibatan mereka. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam dengan pengurus masjid, pengamatan langsung, dan analisis dokumentasi. Hasil penelitian menunjukkan bahwa strategi inovasi yang efektif meliputi penyelenggaraan program yang sesuai dengan minat generasi muda, pemanfaatan media sosial sebagai sarana komunikasi dan promosi, serta kolaborasi dengan komunitas lokal. Implementasi strategi ini terbukti meningkatkan kehadiran dan partisipasi aktif generasi muda dalam kegiatan masjid. Temuan ini diharapkan dapat menjadi referensi bagi masjid-masjid lain dalam mengembangkan strategi yang relevan untuk merangkul generasi muda di lingkungan keagamaan.Kata Kunci: makan gratis, generasi muda, cinta masjid